EFEKTIVITAS PENGGUNAAN SISTEM APLIKASI OTENTIKASI PENERIMA PENSIUN PT.TASPEN SECARA DIGITAL DENGAN MENGGUNAKAN SMARTPHONE DI KOTA PADANG - Adek Nurhasana; Aldri Frinaldi (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2020)
This study aimed to determine the effectiveness of using the PT Taspen digitally using a smartphone in Padang City. Application Authentication is one way to authenticate so that retirees do not have to come to the Bank or Post to collect pension money. This research is are qualitative research that uses descriptive methods. The informants in this study were selected using purposive sampling technique, amounting to 9 informants, namely Taspen employees, Bank Nagari payment partners, pension participants and Information Technology parties. Research instruments in data the form of interviews, observation, and documentation study. The data validity testing technique used the triangulation method. While the data analysis technique is done by reducing data, displaying data, and drawing conclusions and predetermined studies. The results showed the effectiveness of using the PT Taspen digitally using a smartphone in Padang City has not been effective.